Bank behavior based on internal credit ratings of borrowers - Achim Machauer; Martin Weber (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
This study examines the relation of bank loan terms like interest rates, collateral, and lines of credit to borrower risk defined by the banks' internal credit rating. The analysis is not restricted to a static view. It also incorporates rating transition and its implications on the relation. Money illusion and phenomena linked with relationship banking are discovered as important factors. The results show that riskier borrowers pay higher loan rate premiums and rely more on bank finance. Housebanks obtain more collateral and provide more finance. Caused by money illusion in times of high market interest rates loan rate premiums are relatively small whereas in times of low market interest rates they are relatively high. There was no evidence for an appropriate adjustment of loan terms to rating changes. But bank market power represented by a weighted average of credit rating before and after a rating transition serves to compensate for low earlier profits caused by phenomena of interest rate smoothing.
urn:nbn:de:hebis:30-9471
Keywords: G21; 330; Bank loan terms; Internal borrower rating; Relationship banking; Money Illusion